Drug‐coated balloon: Long‐term outcome from a real world three‐center experience. (5th June 2017) - Zivelonghi, Carlo; Ghione, Matteo; Benfari, Giovanni; Cuman, Magdalena; Fede, Alfredo; Lunardi, Mattia; Cordone, Stefano; Botta, Marco; Pacchioni, Andrea; Bellone, Pietro; Reimers, Bernhard; Ribichini, Flavio L.
Abstract : Objectives: In‐stent restenosis (ISR) and diffuse small vessel disease still represent challenging subsets for percutaneous coronary interventions, also in the new‐generation DES era. We aim at reporting on the long‐term clinical outcome of drug‐coated balloons (DCB) in all‐comers population. Methods: Consecutive patients treated with DCB between January 2011 and December 2014 were retrospectively studied in three centers of northern Italy. The measured end‐points were cardiac death, myocardial infarction (MI), target lesion revascularization (TLR), and major adverse cardiac events (MACE) defined as combination of cardiac death, MI, and TLR. Results: We included 143 patients. Of the 167 lesions treated, 41 (24.5%) were de novo lesions in small coronary vessels (<2.5 mm) and 126 (75.4%) were ISR. Among ISR lesions, 78.5% were DES‐ISR, 32.5% were focal, 15.8% multifocal, 30.1% diffuse, 18.2% proliferative, and 3.1% were total occlusions. Procedural success was achieved in 94.6% of cases. Overall survival free from MACEs was 91.6% at 12 months, and 75.3% at 48 months, with a total of 3 cardiac deaths, 8 MI, and 27 TLR. No thrombotic event occurred in the treated segments. There were no differences in MACESs between the ISR and de novo lesions groups. At multivariate analysis, acute coronary syndromes, previous MI, previous surgical revascularization, peripheral arterial disease and diabetes were independent predictors of MACEs at long‐term follow‐up. Conclusions: DCB proved a valid revascularization strategy in an all‐comers population of patients with ISR and de novo lesions in small vessels, with an acceptable rate of cardiac events up to 48 months follow‐up.